Vague Language and Political Rhetoric in Joko Widodo's Speech: Enhancing Critical Thinking in Digital Literacy Contexts - Putri, Irstei Aulia; Jismulatif; Supriusman (Proceeding International Conference on Education, 2025)
This research examines the presence and function of vague language in the political speeches of Joko Widodo, with a focus on its implications for critical thinking and digital literacy. Vague language, including non-specific references, generalizations, and implicit meanings, is a common feature of political rhetoric that can obscure meaning and influence interpretation. The study uses a qualitative content analysis approach to identify the linguistic forms and rhetorical strategies used in selected speeches. Findings indicate that vagueness is employed to maintain flexibility in meaning, appeal to a broad audience, and avoid direct claims that may be politically sensitive. These rhetorical choices present both challenges and opportunities for listeners and readers in digital environments, where information is rapidly disseminated and consumed. By analysing these features in educational settings, students can develop critical thinking skills necessary to decode political texts, evaluate credibility, and make informed judgments. This study argues for the integration of linguistic and rhetorical awareness into digital literacy programs to cultivate more discerning and informed citizens in the digital era.